The spider genus Diguetia Simon, 1895 (Araneae: Diguetidae) in North America: a new species, redescriptions, and comments on the distribution of the genus - Jimenez, Maria-Luisa; Cardiel, Carlos Palacios; Chamé-Vázquez, David (Zootaxa, 2022)
A new species of the genus Diguetia Simon, 1895, D. balandra sp. nov. is described, the male of D. signata Gertsch, 1958 is described for the first time and D. dialectica Chamberlin, 1924 stat. reval. is raised to the species level and redescribed based on specimens from Baja California Sur, Mexico. Diguetia imperiosa Gertsch & Mulaik, 1940 is recorded from Baja California Sur. Furthermore, we emend the diagnosis of the genus, biogeographic comments for all North American species. In the United States, California (five species) and Arizona (four species) have more species of Diguetia while the Mexican states of Sonora (five species), Chihuahua, Baja California, Baja California Sur (four species each) and Coahuila (three species) harbor the highest diversity of diguetids. Diguetia canities (McCook, 1890) has the highest number of records (133) in North America. Mexico has a striking diversity of Diguetia with eight out of ten species currently known.